ANALISIS GERAK DAN LAGU TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI PAUD CIKAL - Heni Nuraeni; Mutoharoh; Euis Rusmalina (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
This study aims to determine the effect of movement and song activities on the gross motor development of 4-5-year-old children at Cikal Preschool. The results indicate that movement and song activities have a positive impact on improving children's gross motor skills, such as jumping, running, and maintaining balance. These activities align with gross motor development theory, which emphasizes the importance of rhythmic and enjoyable activities for optimal development of children's large muscles. Research also shows that learning involving hands-on experiences and active play is highly effective for early childhood. The learning process at Cikal Preschool is conducted through preparation, implementation, and evaluation stages, which systematically assist in monitoring children's motor development. Despite challenges such as differences in developmental speed among children, overall, movement and song activities have proven beneficial in stimulating gross motor development in a fun and meaningful way.